AN INTRODUCTION TO DNA TECHNOLOGIES AND THEIR ROLE IN LIVESTOCK PRODUCTION: A REVIEW - S. Ahmed; A. N. Khosa (Journal of Animal and Plant Sciences, 2010)
DNA technologies have revolutionalized modern science in many ways. DNA (Deoxyribonucleic acid), the hereditary material in all living organism from bacteria to bull, controls and directs all the functions of a living organism. Many techniques have been evolved to understand and manipulate the DNA for many purposes like parentage analysis, curing genetic diseases, forensics, gene therapy and to improve the livestock production. In this paper DNA technologies. Polymerase Chain Reaction (PCR), DNA sequencing, Recombinant DNA technology, DNA microarray technology, marker assisted selection (MAS), stem cell, genetic engineering and their role in order to improve livestock production are reviewed.
Keywords: Deoxyribo nucleic acid (DNA); Short tandem repeat (STR); Single nucleotide polymorphism (SNP); Marker assisted selection (MAS); Polymerase chain reachin (PCR).